2007
DOI: 10.1038/labinvest.3700559
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis in transgenic mice expressing murine amyloidogenic apolipoprotein A-II (Apoa2)

Abstract: In mice, apolipoprotein A-II (apoA-II) self-associates to form amyloid fibrils (AApoAII) in an age-associated manner. We postulated that the two most important factors in apoA-II amyloidosis are the Apoa2 c allele, which codes for the amyloidogenic protein APOA2C (Gln5, Ala38) and transmission of amyloid fibrils. To characterize further the contribution of the Apoa2 c allele to amyloidogenesis and improve detection of amyloidogenic materials, we established transgenic mice that overexpress APOA2C protein under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 51 publications
1
31
2
Order By: Relevance
“…We could not explain the mechanisms underlying the reduced amyloidogenicity of APOA2B from the in vivo polymerization analysis. Genetic analyses suggested that higher levels of cholesterol and larger particles of HDL were present in the plasma of mice with APOA2B compared with mice with APOA2C (15,34) and that it was due to an Ala-to-Val substitution at position 38 (35). In fact, we found that i.v.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…We could not explain the mechanisms underlying the reduced amyloidogenicity of APOA2B from the in vivo polymerization analysis. Genetic analyses suggested that higher levels of cholesterol and larger particles of HDL were present in the plasma of mice with APOA2B compared with mice with APOA2C (15,34) and that it was due to an Ala-to-Val substitution at position 38 (35). In fact, we found that i.v.…”
Section: Discussionsupporting
confidence: 47%
“…ApoA-II proteins in plasma are primarily distributed in HDL 3 particles (15,32). To determine the effects of the polymorphism of apoA-II protein on lipoprotein distribution, we examined the properties of HDL and levels of ApoAs and cholesterols in B6.SPRET-Apoa2 f mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations